Regional Controls on Physical Habitat Structure of Amazon Streams. (15th February 2017) - Benone, N. L.; Esposito, M. C.; Juen, L.; Pompeu, P. S.; Montag, L. F. A.
Abstract: Drainage basins are inherently hierarchical and are composed of a series of nested subsystems, in which the functions and structure of lower levels depend on the features of higher levels. For a comprehensive understanding of the functioning of river systems, it is necessary to identify which factors are important at different scales and how they interact. Considering the importance of assessing lotic systems in the Amazon, our aim was to answer the following question: how do regional features at catchment scale constrain local physical habitat of streams? We sampled 55 streams distributed among six protected river basins of the Amazon, examining the associations of 11 catchment metrics with 146 local variables describing physical habitat structure derived from field measurements. Multivariate analyses showed that basins were structured according to different factors at both scales; variables related to substrate, cover for aquatic organisms and fast channel habitats were explained by altitude, catchment slope and proportion of coarse fragments in soils. Altitude was the most important catchment variable, strongly affecting flow velocity and regulating channel morphology and sediment transport. Spatial differences in environmental heterogeneity indicate that different processes act at each scale; this emphasizes how difficult it is to choose the most relevant spatial scale in ecological studies. Our results highlight the importance of regional variables, especially altitude and slope, as drivers of local‐scale environmental heterogeneity. We hope these results will help in developing more efficient monitoring projects and restoration practices to better understand and conserve aquatic resources in the Amazon Basin. Copyright © 2017 John Wiley & Sons, Ltd.